Concurrent small intestinal neoplasia and large colon volvulus in a standardbred yearling - V. Barros; J. Cascais; K. Holbert; R. Ruby; R. Freeland (Journal of Equine Veterinary Science, 2026)

Disparities in Gallbladder Cancer: Epidemiology, Molecular Mechanisms, and Clinical Implications - Om Saswat Sahoo; Gurpeet Singh Gill; Arnab Nayek; Nidhi Bhardwaj; Kailash Chand Kurdia; Saurabh Galodha; R Chetan; Ruby Dhar; Subhradip Karmakar (Molecular Biology Reports, 2026)

Evolutionary co-option of endogenous retroviruses: syncytins as regulators of placental development and disease - Anamta Gul; Om Saswat Sahoo; Neha Kashyap; Sunil Singh; Anubhuti Rana; Lavanya Gupta; Swati Ajmeriya; Indrani Mukherjee; Ruby Dhar; Nihar R. Nayak; Subhradip Karmakar (Molecular Biology Reports, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Pharmacokinetics and bioavailability of cefuroxime in Nile tilapia (Oreochromis niloticus) - Orhan Corum; Duygu Durna Corum; Pedro Marin; Onder Yildirim; Ertugrul Terzi; Ruby C. Gonzales; Dan M. Arriesgado; Victor R. Navarro; Soner Bilen; Adem Yavuz Sonmez; Kamil Uney (Veterinary Research Communications, 2026)

A framework for context-aware climate risk assessments - Ruby Leigh; Seth Westra; Holger R. Maier; Matthew J. Knowling; Sam Culley; Katherine A. Daniell; Ariella Helfgott; Ashley Kingsborough; Peta Brettig (Journal of Hydrology, 2025)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Air pollution exposures and adverse childhood experiences in relation to sleep health in middle childhood - Jonika B. Hash; Logan C. Dearborn; Christine T. Loftus; Catherine J. Karr; Adam A. Szpiro; Emily S. Barrett; Kaja Z. LeWinn; Ruby Nguyen; Paul E. Moore; Brent Collett; Amanda N. Noroña-Zhou; Nicole R. Bush; et al. (International Journal of Hygiene and Environmental Health, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Tundra Vegetation Community Type, Not Microclimate, Controls Asynchrony of Above‐ and Below‐Ground Phenology - Elise C. Gallois; Isla H. Myers‐Smith; Colleen M. Iversen; Verity G. Salmon; Laura L. Turner; Ruby An; Sarah C. Elmendorf; Courtney G. Collins; Madelaine J. R. Anderson; Amanda Young; Lisa Pilkinton; Gesche Blume‐Werry; et al. (Global Change Biology, 2025)
The below‐ground growing season often extends beyond the above‐ground growing season in tundra ecosystems and as the climate warms, shifts in growing seasons are expected. However, we do not yet know to what extent, when and where asynchrony in above‐ and below‐ground phenology occurs and whether variation is driven by local vegetation communities or spatial variation in microclimate. Here, we combined above‐ and below‐ground plant phenology metrics to compare the relative timings and magnitudes of leaf and fine‐root growth and senescence across microclimates and plant communities at five sites across the Arctic and alpine tundra biome. We observed asynchronous growth between above‐ and below‐ground plant tissue, with the below‐ground season extending up to 74% (~56 days) beyond the onset of above‐ground leaf senescence. Plant community type, rather than microclimate, was a key factor controlling the timing, productivity, and growth rates of fine roots, with graminoid roots exhibiting a distinct ‘pulse’ of growth later into the growing season than shrub roots. Our findings indicate the potential of vegetation change to influence below‐ground carbon storage as the climate warms and roots remain active in unfrozen soils for longer. Taken together, our findings of increased root growth in soils that remain thawed later into the growing season, in combination with ongoing tundra vegetation change including increased shrub and graminoid abundance, indicate increased below‐ground productivity and altered carbon cycling in the tundra biome.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Influence of raceway based biofloc system on the growth and physiological responses of Penaeus vannamei and GIF tilapia in a polyculture model – BFT aquaculture system - M Joshna; Ahilan B; Cheryl Antony; Ravaneswaran K; Chidambaram P; Uma A; Ruby P; Prabu E; Somu Sunder Lingam R (Aquacultural Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Associations of prenatal ambient air pollution exposures with asthma in middle childhood - Marnie F. Hazlehurst; Kecia N. Carroll; Paul E. Moore; Adam A. Szpiro; Margaret A. Adgent; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Yu Ni; Qi Zhao; Emily S. Barrett; Ruby H.N. Nguyen; et al. (International Journal of Hygiene and Environmental Health, 2024)

Unconfined fishway design, implementation, and assessment for the emerald Shiner (Notropis atherinoides) in the Upper Niagara River, New York - Jundong Qiao; Sean J. Bennett; Joseph F. Atkinson; Paul A. Cocca; Sarah K. Delavan; Andrew R. Hannes; Bryan A. Hinterberger; Timothy J. Pede; Alicia Pérez-Fuentetaja; Richard J. Ruby (Ecological Engineering, 2024)

Insulin-like peptides and ovary ecdysteroidogenic hormone differentially stimulate physiological processes regulating egg formation in the mosquito Aedes aegypti - Kangkang Chen; Xiaoyi Dou; Jai Hoon Eum; Ruby E. Harrison; Mark R. Brown; Michael R. Strand (Insect Biochemistry and Molecular Biology, 2023)

Hydrolysate production from sugarcane bagasse using steam explosion and sequential steam explosion-dilute acid pretreatment for polyhydroxyalkanoate fermentation - Hazel Joy C. Barrameda; Princess J. Requiso; Catalino G. Alfafara; Fidel Rey P. Nayve Jr.; Ruby Lynn G. Ventura; Jey-R S. Ventura (Bioactive Carbohydrates and Dietary Fibre, 2023)

Prenatal bisphenol A and S exposure and atopic disease phenotypes at age 6 - Abigail Gaylord; Emily S. Barrett; Sheela Sathyanarayana; Shanna H. Swan; Ruby H.N. Nguyen; Nicole R. Bush; Kecia Carroll; Drew B. Day; Kurunthachalam Kannan; Leonardo Trasande (Environmental Research, 2023)

The population structure, sex ratio and reproductive potential of limpets (Patella spp.) on natural shores and artificial structures in the Irish Sea - Hannah S. Earp; Ruby George; Paul R. Brooks; Veronica Farrugia Drakard; Bryan J. Thompson; Benjamin Fisher; Róisín Hayden; Tasman P. Crowe; Pippa J. Moore (Marine Environmental Research, 2023)

Prenatal exposure to polycyclic aromatic hydrocarbons is not associated with behavior problems in preschool and early school-aged children: A prospective multi-cohort study - Erin R. Wallace; Erin Buth; Adam A. Szpiro; Yu Ni; Christine T. Loftus; Erin Masterson; Drew B. Day; Bob Z. Sun; Alexis Sullivan; Emily Barrett; Ruby HN. Nguyen; Morgan Robinson; et al. (Environmental Research, 2023)

Plasma and muscle tissue disposition of enrofloxacin in Nile tilapia ( Oreochromis niloticus ) after intravascular, intraperitoneal, and oral administrations - Orhan Corum; Ertugrul Terzi; Duygu Durna Corum; Yigit Tastan; Ruby C. Gonzales; Osman Nezih Kenanoglu; Dan M. Arriesgado; Victor R. Navarro; Soner Bilen; Adem Yavuz Sonmez; Kamil Uney (Food Additives & Contaminants: Part A, 2022)

Seaweed ethnobotany of eastern Sorsogon, Philippines - Richard V. Dumilag; Teresa Haide R. Belgica; Lynn C. Mendoza; Janet M. Hibay; Abel E. Arevalo; Mark Ariel D. Malto; Elden G. Orgela; Mabille R. Longavela; Laurence Elmer H. Corral; Ruby D. Olipany; Caesar Franz C. Ruiz; Cynthia B. Mintu; et al. (Algae, 2022)
Knowledge on the seaweeds of eastern Sorsogon in the Philippines is uneven. Not only is eastern Sorsogon among the areas of high seaweed diversity but locals there have interacted with seaweeds for ages. Despite seaweeds’ assumed importance to Sorsoganon, ethnobotanical records are missing. In this study, we documented the traditional knowledge on seaweed use and determined the rate of knowledge transmission among the locals of eastern Sorsogon. Vernacular names and modes of preparation were given of the 12 identified species bearing culinary and medicinal importance. Ten species were eaten while three were used therapeutically. Based on ethnobotanical indices, Caulerpa chemnitzia ecad turbinata and Gelidiella acerosa were the most important seaweeds. The least cited was Caulerpa racemosa. Our study demonstrated that most of the seaweed resources in eastern Sorsogon remain largely untapped, as the identified ethnotaxa were only about 5% of the total seaweed species diversity reported for the area. The seaweed knowledge in eastern Sorsogon appeared to be homogenous across age groups with primary sources of knowledge biased towards female relatives (mothers and grandmothers) and to children as inheritors. Cessation of seaweed knowledge may come at a potential cost, as a significant fraction of the population did not transmit their knowledge to others. Our study furthered the interest in providing sophisticated resource management recommendations that consider the relationships of traditional and scientific knowledge of seaweed selection and use in eastern Sorsogon and beyond.

Climate shapes community flowering periods across biomes - Ruby E. Stephens; Hervé Sauquet; Greg R. Guerin; Mingkai Jiang; Daniel Falster; Rachael V. Gallagher (Journal of Biogeography, 2022)
Aim Climate shapes the composition and function of plant communities globally, but it remains unclear how this influence extends to floral traits. Flowering phenology, or the time period in which a species flowers, has well‐studied relationships with climatic signals at the species level but has rarely been explored at a cross‐community and continental scale. Here, we characterise the distribution of flowering periods (months of flowering) across continental plant communities encompassing six biomes, and determine the influence of climate on community flowering period lengths. Location Australia. Taxon Flowering plants. Methods We combined plant composition and abundance data from 629 standardised floristic surveys (AusPlots) with data on flowering period from the AusTraits database and additional primary literature for 2983 species. We assessed abundance‐weighted community mean flowering periods across biomes and tested their relationship with climatic annual means and the predictability of climate conditions using regression models. Results Combined, temperature and precipitation (annual mean and predictability) explain 29% of variation in continental community flowering period. Plant communities with higher mean temperatures and lower mean precipitation have longer mean flowering periods. Moreover, plant communities in climates with predictable temperatures and, to a lesser extent, predictable precipitation have shorter mean flowering periods. Flowering period varies by biome, being longest in deserts and shortest in alpine and montane communities. For instance, desert communities experience low and unpredictable precipitation and high, unpredictable temperatures and have longer mean flowering periods, with desert species typically flowering at any time of year in response to rain. Main conclusions Current climate conditions shape flowering periods across biomes, with implications for phenology under climate change. Shifts in flowering periods across climatic gradients reflect changes in plant strategies, affecting patterns of plant growth and reproduction as well as the availability of floral resources for pollinators across the landscape.

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Efficient production of fatty acid methyl esters by a wastewater-isolated microalgae-yeast co-culture - Jessica K. Suastes-Rivas; Raúl Hernández-Altamirano; Violeta Y. Mena-Cervantes; Ruby Valdez-Ojeda; Tanit Toledano-Thompson; Luis R. Tovar-Gálvez; Silvia López-Adrián; Isaac Chairez (Environmental Science and Pollution Research, 2020)

North American extreme precipitation events and related large-scale meteorological patterns: a review of statistical methods, dynamics, modeling, and trends - Mathew Barlow; William J. Gutowski; John R. Gyakum; Richard W. Katz; Young-Kwon Lim; Russ S. Schumacher; Michael F. Wehner; Laurie Agel; Michael Bosilovich; Allison Collow; Alexander Gershunov; Richard Grotjahn; et al. (Climate Dynamics, 2019)
This paper surveys the current state of knowledge regarding large-scale meteorological patterns (LSMPs) associated with short-duration (less than 1 week) extreme precipitation events over North America. In contrast to teleconnections, which are typically defined based on the characteristic spatial variations of a meteorological field or on the remote circulation response to a known forcing, LSMPs are defined relative to the occurrence of a specific phenomenon—here, extreme precipitation—and with an emphasis on the synoptic scales that have a primary influence in individual events, have medium-range weather predictability, and are well-resolved in both weather and climate models. For the LSMP relationship with extreme precipitation, we consider the previous literature with respect to definitions and data, dynamical mechanisms, model representation, and climate change trends. There is considerable uncertainty in identifying extremes based on existing observational precipitation data and some limitations in analyzing the associated LSMPs in reanalysis data. Many different definitions of “extreme” are in use, making it difficult to directly compare different studies. Dynamically, several types of meteorological systems—extratropical cyclones, tropical cyclones, mesoscale convective systems, and mesohighs—and several mechanisms—fronts, atmospheric rivers, and orographic ascent—have been shown to be important aspects of extreme precipitation LSMPs. The extreme precipitation is often realized through mesoscale processes organized, enhanced, or triggered by the LSMP. Understanding of model representation, trends, and projections for LSMPs is at an early stage, although some promising analysis techniques have been identified and the LSMP perspective is useful for evaluating the model dynamics associated with extremes.

Workers' sons rescue genetic diversity at the sex locus in an invasive honey bee population - Rosalyn S. Gloag; Joshua R. Christie; Guiling Ding; Ruby E. Stephens; Gabriele Buchmann; Benjamin P. Oldroyd (Molecular Ecology, 2019)
The hallmark of eusociality is the division of labour between reproductive (queen) and nonreproductive (worker) females. Yet in many eusocial insects, workers retain the ability to produce haploid male offspring from unfertilized eggs. The reproductive potential of workers has well‐documented consequences for the structure and function of insect colonies, but its implications at the population level are less often considered. We show that worker reproduction in honey bees can have an important role in maintaining genetic diversity at the sex locus in invasive populations. The honey bee sex locus is homozygous‐lethal, and, all else being equal, a higher allele number in the population lead to higher mean brood survival. In an invasive population of the honey bee Apis cerana in Australia, workers contribute significantly to male production: 38% of male‐producing colonies are queenless, and these contribute one‐third of all males at mating congregations. Using a model, we show that such male production by queenless workers will increase the number of sex alleles retained in nascent invasive populations following founder events, relative to a scenario in which only queens reproduce. We conclude that by rescuing sex locus diversity that would otherwise be lost, workers' sons help honey bee populations to minimize the negative effects of inbreeding after founder events and so contribute to their success as invaders.

Effects of seasonal and environmental changes on aquaculture production in tropical Lake Volta, Ghana - Emmanuel T. D. Mensah; Hederick R. Dankwa; Lauridsen L. Torben; Ruby Asmah; Benjamin B. Campion; Regina Edziyie (Aquaculture International, 2018)

Transcriptional characterization of Vibrio fischeri during colonization of juvenile Euprymna scolopes - Luke R. Thompson; Kiel Nikolakakis; Shu Pan; Jennifer Reed; Rob Knight; Edward G. Ruby (Environmental Microbiology, 2017)
Summary The marine bacterium Vibrio fischeri is the monospecific symbiont of the Hawaiian bobtail squid, Euprymna scolopes , and the establishment of this association involves a number of signaling pathways and transcriptional responses between both partners. We report here the first full RNA‐Seq dataset representing host‐associated V. fischeri cells from colonized juvenile E. scolopes , as well as comparative transcriptomes under both laboratory and simulated marine planktonic conditions. These data elucidate the broad transcriptional changes that these bacteria undergo during the early stages of symbiotic colonization. We report several previously undescribed and unexpected transcriptional responses within the early stages of this symbiosis, including gene expression patterns consistent with biochemical stresses inside the host, and metabolic patterns distinct from those reported in associations with adult animals. Integration of these transcriptional data with a recently developed metabolic model of V. fischeri provides us with a clearer picture of the metabolic state of symbionts within the juvenile host, including their possible carbon sources. Taken together, these results expand our understanding of the early stages of the squid–vibrio symbiosis, and more generally inform the transcriptional responses underlying the activities of marine microbes during host colonization.

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Future hurricane storm surge risk for the U.S. gulf and Florida coasts based on projections of thermodynamic potential intensity - Karthik Balaguru; David R. Judi; L. Ruby Leung (Climatic Change, 2016)

Circulating microRNA Signatures in Rodent Models of Pain - Rehman A. Qureshi; Yuzhen Tian; Marguerite K. McDonald; Kathryn E. Capasso; Sabrina R. Douglas; Ruby Gao; Irina A. Orlova; James E. Barrett; Seena K. Ajit; Ahmet Sacan (Molecular Neurobiology, 2016)

North American extreme temperature events and related large scale meteorological patterns: a review of statistical methods, dynamics, modeling, and trends - Richard Grotjahn; Robert Black; Ruby Leung; Michael F. Wehner; Mathew Barlow; Mike Bosilovich; Alexander Gershunov; William J. Gutowski; John R. Gyakum; Richard W. Katz; Yun-Young Lee; Young-Kwon Lim; et al. (Climate Dynamics, 2016)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Cytotoxicity studies of semi-synthetic derivatives of theveside derived from the aqueous extract of leaves of ‘suicide tree’ Cerbera odollam - Jaggaiah N. Gorantla; Jamsheena Vellekkatt; Lekshmi R. Nath; Ruby John Anto; Ravi S. Lankalapalli (Natural Product Research, 2014)

Molecular cloning and characterization of genistein 4′-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; R. J. Santosh Kumar; Rishi K. Vishwakarma; Somesh Singh; Bashir M. Khan (Molecular Biology Reports, 2014)

Functional Characterization of a Glucosyltransferase Specific to Flavonoid 7-O-Glucosides from Withania somnifera - R. J. Santosh Kumar; Ruby; Somesh Singh; Prashant D. Sonawane; R. K. Vishwakarma; B. M. Khan (Plant Molecular Biology Reporter, 2013)

Synthesis of piperazinyl benzothiazole/benzoxazole derivatives coupled with 1,3,4-oxadiazole-2-thiol: novel hybrid heterocycles as anticancer agents - M. S. R. Murty; B. Ramalingeswara Rao; Mohana Rao Katiki; Lekshmi R. Nath; Ruby John Anto (Medicinal Chemistry Research, 2013)

Molecular Cloning, Biochemical Characterization, and Differential Expression of an Acetyl-CoA C-Acetyltransferase Gene (AACT) of Brahmi (Bacopa monniera) - Rishi K. Vishwakarma; Ruby; Somesh Singh; Prashant D. Sonawane; Sameer Srivastava; Uma Kumari; R. J. Santosh Kumar; Bashir M. Khan (Plant Molecular Biology Reporter, 2013)

Synthesis and preliminary evaluation activity studies of novel 4-(aryl/heteroaryl-2-ylmethyl)-6-phenyl-2-[3-(4-substituted-piperazine-1-yl)propyl]pyridazin-3(2H)-one derivatives as anticancer agents - M. S. R. Murty; B. Ramalingeswara Rao; Kesur R. Ram; J. S. Yadav; Jayesh Antony; Ruby John Anto (Medicinal Chemistry Research, 2012)

Substrate use and biochemical response to a 3,211-km bicycle tour in trained cyclists - Dustin R. Slivka; Charles L. Dumke; Walter S. Hailes; John S. Cuddy; Brent C. Ruby (European Journal of Applied Physiology, 2012)

Synthesis and preliminary evaluation of 2-substituted-1,3-benzoxazole and 3-[(3-substituted)propyl]-1,3-benzoxazol-2(3H)-one derivatives as potent anticancer agents - M. S. R. Murty; Kesur R. Ram; Rayudu Venkateswara Rao; J. S. Yadav; Janapala Venkateswara Rao; Vino T. Cheriyan; Ruby John Anto (Medicinal Chemistry Research, 2011)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Non-coding RNAs revealed during identification of genes involved in chicken immune responses - Marie-Laure Endale Ahanda; Thomas Ruby; Håkan Wittzell; Bertrand Bed’Hom; Anne-Marie Chaussé; Veronique Morin; Anne Oudin; Catherine Chevalier; John R. Young; Rima Zoorob (Immunogenetics, 2009)

Separation of rifting and lithospheric folding signatures in the NW-Alpine foreland - O. Bourgeois; M. Ford; M. Diraison; C. Le Carlier de Veslud; M. Gerbault; R. Pik; N. Ruby; S. Bonnet (International Journal of Earth Sciences, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Elevation Dependence of Winter Wheat Production in Eastern Washington State with Climate Change: A Methodological Study - Allison M. Thomson; Robert A. Brown; Steven J. Ghan; R. Cesar Izaurralde; Norman J. Rosenberg; L. Ruby Leung (Climatic Change, 2002)

Sublethal Lead Affects Pituitary Function of Rainbow Trout During Exogenous Vitellogenesis - S. M. Ruby; R. Hull; P. Anderson (Archives of Environmental Contamination and Toxicology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Tuber yield, soft rot resistance, bruising resistance and processing quality in a population of potato (cv. crystal) somaclones - R. J. Taylor; G. A. Secor; C. L. Ruby; P. H. Orr (American Journal of Potato Research, 1993)

Plasma vitellogenin levels in pre-spawning rainbow trout,Oncorhynchus mykiss, during acid exposure - Robert L. Roy; Sylvia M. Ruby; David R. Idler; Ying So (Archives of Environmental Contamination and Toxicology, 1990)

Changes in plasma, liver, and ovary vitellogenin in landlocked atlantic salmon following exposure to sublethal cyanide - Sylvia M. Ruby; David R. Idler; Ying Peng So (Archives of Environmental Contamination and Toxicology, 1987)

The effect of sublethal cyanide exposure on plasma viteliogenin levels in rainbow trout (Salmo gairdneri) during early vitellogenesis - Sylvia M. Ruby; David R. Idler; Ying Peng So (Archives of Environmental Contamination and Toxicology, 1986)